Investigation of Structural, Optical Characteristics, and Morphological Properties, as well as the Antibacterial Efficacy of MgO˗Bi2-xAgxO3 Nanocomposites Synthesized via the Solvent-Deficient Method (Thamar University Journal of Natural & Applied Sciences, 2025)
In this work, MgO–Bi2₋xAgxO3 nanocomposites with different silver contents (x = 0.00, 0.03, 0.05, and 0.07) were synthesized using a simple solvent-deficient method. The structural, optical, morphological, and antibacterial properties of the prepared materials were systematically investigated. X-ray diffraction analysis confirmed that all samples crystallized in the monoclinic α-Bi2O3 phase, with no detectable secondary phases related to MgO or AgO, suggesting that these components were either highly dispersed or present in an amorphous form. The average crystallite size was found to increase with Ag content up to x = 0.05, followed by a slight decrease at x = 0.07. Scanning electron microscopy revealed agglomerated particles with relatively uniform distribution, while silver doping led to noticeable improvements in surface morphology. Energy-dispersive X-ray spectroscopy confirmed the presence of Mg, Bi, O, and Ag in compositions close to the intended stoichiometry. Optical studies based on UV–visible spectroscopy showed that the optical bandgap decreased slightly with increasing Ag content, with values of 3.14, 3.13, 3.10, and 3.11 eV for x = 0.00, 0.03, 0.05, and 0.07, respectively. These changes were attributed to the introduction of Ag-related impurity states within the band structure. The antibacterial activity of the nanocomposites was evaluated against both Gram-negative and Gram-positive bacteria using the disc diffusion method. Silver-doped samples exhibited enhanced antibacterial performance compared with the undoped material, with the highest activity observed for the Ag-containing nanocomposites. Notably, inhibition zones exceeding 23 mm were recorded against Gram-negative bacteria, highlighting the strong antibacterial effect associated with Ag incorporation. Overall, the results demonstrate that MgO–Bi2₋xAgxO3 nanocomposites prepared by the solvent-deficient method possess promising structural, optical, and antibacterial properties, making them potential candidates for applications in medical and environmental fields.